Rice body formation characterized by the chronic non-specific tenosynovitis in the tibialis anterior tendon - Bulut, Mehmet; Yilmaz, Erhan; Karakurt, Lokman; Ozercan, M. Resat (Turkish Assoc Orthopaedics Traumatology, 2013)
In this case report a 38-year-old woman who presented with swelling and pain on her right ankle for two years is presented. Physical and radiological examinations revealed a soft, lobulated and fixed mass in the ankle During surgical resection shiny, whitish bodies were removed from the tendon sheath of tibialis anterior and synovectomy was performed. Histopathological diagnosis was rice body formation and syovitis. There was no recurrence at the 5th year follow-up. Magnetic resonance imaging was effective in the diagnosis of this rare case of extra articular rice body formation presenting with tenosynovitis and full recovery was achieved with surgical treatment.
Keywords: Local resection; rice body formation; tenosynovitis; tibialis anterior